[8+3]‐Cycloaddition of Tropones with Azaoxyallyl Cations. Issue 24 (15th October 2019) - Roy, Tony; Jacob, Anu; Bhattacharjee, Subrata; Biju, Akkattu T.
Abstract: Although azaoxyallyl cations are widely used as 1, 3‐dipoles for various cycloaddition reactions leading to nitrogen‐containing heterocycles, their application in higher‐order cycloaddition reaction remains scarce. Herein, we present the [8+3]‐cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one‐step construction of cycloheptatriene‐fused 1, 4‐oxazinones in moderate to good yields. This base‐promoted new carbon‐oxygen and carbon‐nitrogen bond‐forming reaction takes place under mild conditions in the absence of transition metal catalysts. Abstract : The [8+3]‐cycloaddition reaction of tropones with in situ generated azaoxyallyl cations allowing the one‐step synthesis of cycloheptatriene‐fused oxazinones in moderate to good yields is presented. This base‐promoted new carbon‐oxygen and carbon‐nitrogen bond‐forming reaction takes place under mild conditions in the absence of transition metal catalysts.